New Subclasses of Analytic Functions with Respect to Symmetric and Conjugate Points. (4th February 2013) - Tang, Huo; Deng, Guan-Tie
Abstract : We introduce new subclasses of close-to-convex and quasiconvex functions with respect to symmetric and conjugate points. The coefficient estimates for functions belonging to these classes are obtained.